Employability Perceptions and Experiences of International Students from the Global South (Comparative & International Education Series, 2022)
Though academic and social experiences of international students have been discussed broadly (Huang, 2018), the employability of international students is not much celebrated in higher education studies (Waters, 2009). To have a better and comprehensive understanding, and then enhance their employability experiences after graduation, we need to know more about international students’ career intentions, attitudes, and experiences. Therefore, this study attempts to identify the career planning, career developments, and employment experiences of former international students who completed at least one graduate degree in Turkey and/or are currently employed in their home country. Following an interpretative phenomenological design, 10 respondents from the Global South countries were interviewed. The study mainly shows that Turkey experience is significant in perceiving and managing the current or future employability of incoming Global South students. The current research contributes to the understanding of international students’ employment expectations, integration into the market, and developing compatibility across cultures.